Assessing the Level of Work Preparedness of Final-Year BSc Quantity Surveying Students at University of Rwanda - Kibwami, Nathan; Mugiraneza, Phillipe; Ndibwami, Alex; Sheja, Didier (Journal of Educational and Social Research, 2020)
The overarching vision of Higher Learning Institutions that are concerned with construction education, is to nurture graduates that will be prepared to not only deal with the current needs of the Construction Industry, but also be able to immerse themselves confidently in a future full of complexity. However, the transition from University to work is often a daunting experience for graduates, and employers often complain that graduates are usually ill prepared for work. It is therefore important to understand the students’ perspective regarding level of work preparedness so that solutions can be sought, both from Universities and Industry, to make the transition from University to the world of work a truly empowering experience. This study investigated the level of preparedness to start work for final-year students (2019/20) pursuing a Bachelor of Science degree in Quantity Surveying (QSg) at University of Rwanda. An online questionnaire was designed and administered to 59 students to solicit their perceptions. Most students (42%) asserted that they were very prepared to start working as Quantity Surveyors, with some (12%) extremely prepared. Industrial Training stood out as the largest contributor in preparing students to start work, whereas University laboratory resources did not contribute much. Students exhibited most knowledge in core QSg competences, such as Estimating Costs of construction works. Although students were most confident in topics on Measurement of Finishes, students that had a Technical and Vocational Education and Training background exhibited greater confidence. The findings of this study provide important feedback for similar construction programs to evaluate and revise their curricula to better prepare QSg students for professional success in the Construction Industry.
Keywords: Higher learning institutions, quantity surveying, Rwanda, construction education, work preparedness